Menstrual health and factors associated with school absence among secondary school girls in Luang Prabang Province, Lao People's Democratic Republic: A cross-sectional study. - Souphalak Inthaphatha; Viengsakhone Louangpradith; Leyla Isin Xiong; Valee Xiong; Ly Ly; Vue Xaitengcha; Alongkone Phengsavanh; Nobuyuki Hamajima; Eiko Yamamoto (PLoS ONE)
In Lao People's Democratic Republic (Lao PDR), information on school sanitation and menstrual health among secondary school girls is limited. This study aimed to explore knowledge and practices surrounding menstrual health and to identify factors associated with school absence due to menstruation among secondary school girls in Lao PDR. The study involved 1,366 girls from grade 9 to grade 12 in six secondary schools in Luang Prabang Province. Data on socio-demographics and menstrual health of the girls and data on school toilets was collected. Logistic regression analysis was performed to identify the factors associated with school absence due to menstruation. The mean age was 15.8 years old. The average age of menarche was 12.9 years old. Of 1,366 girls, 64.6% were shocked or ashamed when they reached menarche and 31.8% had been absent from school due to menstruation in the six months before this study was conducted. Factors associated with school absence due to menstruation were age ≥ 16 years old (AOR = 1.79, 95% CI 1.37-2.34), higher income (AOR = 2.38, 95% CI 1.16-4.87), menstrual anxiety (AOR = 1.55, 95% CI 1.09-2.20), using painkillers (AOR = 4.79, 95% CI 2.96-7.76) and other methods (AOR = 2.82, 95% CI 1.86-4.28) for dysmenorrhea, and disposing used pads in places other than the school's waste bins (AOR = 1.34, 95% CI 1.03-1.75). Living with relatives (AOR = 0.64, 95% CI 0.43-0.95) and schools outside the city (AOR = 0.59, 95% CI 0.38-0.90) were significantly less associated with school absence. Although the association between school toilets and school absence was not examined, the results of this study suggest that school toilets should be gender-separated and equipped with waste bins in the toilet. Furthermore, menstrual education should start at elementary schools and teacher training on menstrual health should be promoted.